ABOUT PROBABILITY OF RESEARCH OF THE NN Ser SPECTRUM BY MODEL ATMOSPHERES METHOD - Sakhibullin, N. A.; Shimansky, V. V. (Одеські астрономічні публікації, 2017)
The spectrum of close binary system NN Ser is investigated by a models atmospheres method. It is show that the atmosphere near the centrum of a hot spot on surface of red dwarf has powerful chromospheres, arising from heating in Laiman continua. Four models of binary system with various of parameters are constructed and their theoretical spectra are obtained. Temperature of white dwarf Tef = 62000 K, radius of the red dwarf RT = 0.20139 and angle inclination of system i = 82“ are determined. The spectrum having the good coincidence with data of observation is received.